Pelatihan Optimalisasi Pemasaran Melalui Media Sosial Berbantuan Ekosistem Digital Ketenagakerjaan Di BBPVP Semarang - Rahayu, Ujiati; Sutarto, Joko (Lembaga Teewan Journal Solutions, 2026)
This study was motivated by the importance of developing digital marketing competencies and workforce readiness in the era of digital transformation through social media-based training. The study aimed to analyze the implementation of social media marketing optimization training supported by a digital employment ecosystem at BBPVP Semarang. This research employed a qualitative approach using a multi case study design. Data were collected through in-depth interviews, participatory observation, and documentation involving training managers, instructors, and trainees selected purposively. Data analysis applied the Miles and Huberman interactive model through data reduction, data display, and conclusion drawing. The findings revealed that Project Based Learning and blended learning approaches improved participants’ digital competencies, social media marketing skills, and entrepreneurial attitudes. The integration of digital practices, social media platforms, and On the Job Training strengthened participants’ job readiness in meeting digital industry demands. Supporting factors included instructor quality, hands-on learning methods, and industrial partnerships, while the main obstacles were limited digital infrastructure and technical system constraints. This study contributes to the development of training and digital marketing theories within the context of vocational training supported by a digital employment ecosystem